Open Appendicectomy . . . How I do it - John Adwok (South Sudan Medical Journal, 2016)
This article is meant for medical officers and surgeons in training who might be called upon to perform this procedure in the absence of a trained general surgeon. The techniques described here are the ones used by the author for this procedure and might differ from those used by other surgeons. However, the principles of the operation are universal. This procedure is predominantly performed laparoscopically in the author’s practice as is the case in most modern hospitals with the necessary equipment and expertise. The open procedure is the standard in many hospitals in developing countries and when there is a need to convert to open during difficult laparoscopic procedures.